2001
DOI: 10.1007/pl00011973
|View full text |Cite
|
Sign up to set email alerts
|

Spinal tuberculosis (Pott’s disease): its clinical presentation, surgical management, and outcome. A survey study on 694 patients

Abstract: Tuberculosis (TB) of the spine (Pott's disease) is both the most common and most dangerous form of TB infection. Delay in establishing diagnosis and management cause spinal cord compression and spinal deformity. This study investigated the data on all cases of Pott's disease reported in Turkey from 1985 to 1996. A total of 694 cases were included. Out of the patients evaluated, 19% were reported in the first half of the period (1985-1990) and 81% in the second half (1991-1996). Tuberculosis affecting the spine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
215
6
17

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(252 citation statements)
references
References 13 publications
14
215
6
17
Order By: Relevance
“…No other evidence has been published to date from the Neolithic of Italy (Rubini et al, 2014), and sites such as Çatalhöyük, with hundreds of burials, have not reported clear evidence of TB (Knüsel, personal communication 2016). Considering the potential for differential preservation of children's skeletons (Roberts and Buikstra, 2003: 50;Bello et al, 2006), the low percentage of untreated individuals with TB that show skeletal involvement today (1%, Turgut: 2001;3-5%: Vigorita, 1999), and in particular of disseminated TB (4-5% of individuals with skeletal involvement, McTammany et al, 1963), one could speculate that TB must have had a high prevalence during the Neolithic in Liguria. Future research will aim to test this hypothesis, and will attempt to identify the possible risk factors for this population.…”
Section: Significance For Bioarchaeology and Paleoepidemiology Of Tbmentioning
confidence: 99%
“…No other evidence has been published to date from the Neolithic of Italy (Rubini et al, 2014), and sites such as Çatalhöyük, with hundreds of burials, have not reported clear evidence of TB (Knüsel, personal communication 2016). Considering the potential for differential preservation of children's skeletons (Roberts and Buikstra, 2003: 50;Bello et al, 2006), the low percentage of untreated individuals with TB that show skeletal involvement today (1%, Turgut: 2001;3-5%: Vigorita, 1999), and in particular of disseminated TB (4-5% of individuals with skeletal involvement, McTammany et al, 1963), one could speculate that TB must have had a high prevalence during the Neolithic in Liguria. Future research will aim to test this hypothesis, and will attempt to identify the possible risk factors for this population.…”
Section: Significance For Bioarchaeology and Paleoepidemiology Of Tbmentioning
confidence: 99%
“…In the last case, it was not clear if the patient was operated or not [8]. However, in the papers including those cases with multilevel involvement, 34-86% of the patients (totally 64%) required an operation [2,5,8,9]. The higher operation percentage of the multilevel spinal tuberculosis is possibly due to ''fulminant'' behaviour of the disease in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…Non-contiguous multifocal tuberculous spondylitis is rare. Turgut [9] reported only one patient with non-contiguous thoracic and lumbar involvement in 694 patients. Rezai et al [8] reported one patient with thoracic and thoracolumbar involvement in 20 patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations